Pengaruh Minat Belajar dan Motivasi Belajar Terhadap Hasil Belajar pada Mata Pelajaran IPS Siswa Kelas VIII SMP Negeri 2 Siantar: Penelitian - Veni Chrisnawati S.Garingging; Anton Luvi Siahaan; Benjamin Albert Simamora (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of learning interest and learning motivation on the learning outcomes of Social Studies (IPS) among eighth-grade students of SMP Negeri 2 Siantar in the 2024/2025 academic year. This research employed a quantitative approach with multiple linear regression analysis. The population consisted of 91 students of grade VIII, while the sample included 91 students selected using random sampling. The instruments used were questionnaires on learning interest and learning motivation, which were tested for validity and reliability. Data were analyzed using t-test, F-test, and coefficient of determination (R²) with the aid of SPSS 26. The results showed that: (1) learning interest has a positive and significant effect on IPS learning outcomes with tcount 5.504 > ttable 1.987 and significance value 0.000 < 0.05; (2) learning motivation has a positive and significant effect on IPS learning outcomes with tcount 9.065 > ttable 1.987 and significance value 0.000 < 0.05; (3) learning interest and motivation simultaneously have a positive and significant effect on IPS learning outcomes with Fcount 159.485 > Ftable 3.100 and significance value 0.000 < 0.05. The coefficient of determination (R²) was 0.720, meaning that learning interest and motivation contributed 72% to IPS learning outcomes, while the remaining 28% was influenced by other factors not examined in this study.